Foodora and Deliveroo: The App as a Boss? Control and autonomy in app-based management - the case of food delivery riders - Mirela Ivanova; Joanna Bronowicka; Eva Kocher; Anne Degner (Hans-Böckler-Stiftung, 2018)
The rise of digital platforms requires a deeper understanding of the structural role of algorithmic management in work environments. In this interdisciplinary study, we examine how digital platforms, which offer food delivery service, use a mobile application for management of their workforce. Drawing on interviews with self-employed riders at Deliveroo and employed riders at Foodora, we compare how the app affects the interplay between autonomy and control of riders, and how the app-based management relates to different contractual models.
urn:nbn:de:101:1-2019022610132332740779
Keywords: 330; delivery services; algorithm; app-based management; Foodora; Deliveroo